2016
DOI: 10.1371/journal.pone.0165981
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Whole Blood n-3 and n-6 Polyunsaturated Fatty Acids with Blood Pressure in Children and Adolescents – Results from the IDEFICS/I.Family Cohort

Abstract: BackgroundPolyunsaturated n-3 and n-6 polyunsaturated fatty acids (PUFA) are precursors of biologically active metabolites that affect blood pressure (BP) regulation. This study investigated the association of n-3 and n-6 PUFA and BP in children and adolescents.MethodsIn a subsample of 1267 children aged 2–9 years at baseline of the European IDEFICS (Identification and prevention of dietary- and lifestyle-induced health effects in children and infants) cohort whole blood fatty acids were measured by a validate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 68 publications
1
15
1
Order By: Relevance
“…Thus, the unexpected effects of EPA are likely to result from effect modification by weight status. Also in a recent study, we found a beneficial effect of EPA on BP only in thin/normal weight children whereas an unfavorable association was observed in overweight/obese children [18]. We did not consider DHA in our analyses as the conversion efficiency from ALA and EPA to DHA is very low [54, 55] and we were particularly interested in the SNP’s influence on endogenous synthesis via FADS1 and the effects on BP in this analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the unexpected effects of EPA are likely to result from effect modification by weight status. Also in a recent study, we found a beneficial effect of EPA on BP only in thin/normal weight children whereas an unfavorable association was observed in overweight/obese children [18]. We did not consider DHA in our analyses as the conversion efficiency from ALA and EPA to DHA is very low [54, 55] and we were particularly interested in the SNP’s influence on endogenous synthesis via FADS1 and the effects on BP in this analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The hypotensive effect of PUFAs is usually observed in patients aged > 45 years, taking higher doses of PUFAs (above 3-4 g per day) for a duration of > 12 weeks. Likewise, in children, high n-3 PUFA levels were associated with lower BP [10]. Hypotensive effect has also been documented with regard to DHA and EPA.…”
Section: Introductionmentioning
confidence: 89%
“…A higher blood level of ARA is related to higher prevalence of arterial hypertension [153]. The research into the risk of atherosclerosis has revealed that lower LA levels and higher blood levels of ARA correspond to a higher risk of hypertension; moreover, ARA levels directly correlated with the body mass index and related metabolic syndrome [154][155][156].…”
Section: Omega-6 Polyunsaturated Fatty Acidsmentioning
confidence: 99%
“…Myristic acid (C14:0) -↑ the risk of developing IHD; ↑ total cholesterol concentration [32,39] Palmitic acid (C16:0) -↑ production of pro-inflammatory cytokines and oxidants; promotes inflammation and the development of CVD [31,32,[34][35][36][37] ↓ LDL, glucose, arterial blood pressure normalizes [30] Stearic acid (C18:0) ± not correlate with a higher risk of IHD and MI; induces apoptosis and necrosis of endothelial cells; ↑ the risk of developing IHD [27,[44][45][46][47][48] does not have a significant influence on lipid metabolism [10,41] Palmitoleic acid (C16:1) ± ↓ cholesterol and TG concentrations; ↑ HDL cholesterol concentrations [56,57]; ↑ the risk of developing IHD [32] Oleic acid (C18:1) ± can improve the blood lipid profile [65]; ↓ the risk of atherosclerosis [69]; ↑ TG concentrations; ↑ markers of inflammation; ↑ the risk of developing heart failure [36,71] Linoleic acid (C18:2) + ↓ risk developing IHD and death from IHD [140,141]; does not affect the concentrations of inflammatory biomarkers [146,147] ↑ risk of arterial hypertension [154][155][156] α-Linolenic acid (C18:3) + ↓ the risk of death from IHD; ↓ the levels of LDL and total cholesterol; ↑ the levels of HDL [80][81][82];…”
Section: Fatty Acids the Influence On The Cardiovascular System Effecmentioning
confidence: 99%
See 1 more Smart Citation